Geotechnologies in soil loss evaluation - DE SOUZA, Flávia Luize Pereira [UNESP]; Leme, MATEUS DE CAMPOS [UNESP]; Sartori, ANDERSON ANTÔNIO DA CONCEIÇÃO; Manzato, Caroline Lourenço [UNESP]; Sérgio Campos, E. [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2019)
The application of the Universal Soil Loss Equation (USLE) and geoprocessing in the analysis of environmental systems, allows an estimation of soil loss in watersheds favoring environmental zoning and, consequently, environmental planning. Therefore the aim was to evaluate soil losses and erosion risk by means of USLE quantitative model in GIS environment in Alto Batalha river Sub-basin located in the city of Bauru (SP). For the study, the USLE methodology was applied, which lists six factors to quantify the erosion risk in the area, like rain erosion (R), soil erodibility (K), slope length (L), declivity of the slope (S), vegetation cover and conservation practices (CP). Thus, it was found that the highest rates of annual soil loss in Alto Batalha Sub-Basin are correlated with the CP factor, mainly in areas of agriculture and exposed areas, which justifies inadequate management and increasing soil losses. The USLE equation used in the estimation of soil losses allowed the classification of the degree of erodibility (K) in the area. Therefore, it was inferred that Alto Batalha Sub-basin requires care, regarding the control of erosive processes.
Geotecnologias na avaliação de perdas de solo
Keywords: Environmental planning; Erosion; Ground; Management